2015
DOI: 10.1002/ajim.22464
|View full text |Cite
|
Sign up to set email alerts
|

Keeping workers safe: Does provision of personal protective equipment match supervisor risk perceptions?

Abstract: PPE provision was limited by management's poor perceptions of its efficacy relative to other factors. Future research should explore workers' perceptions and PPE's effectiveness in averting horse-related injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…A total of 7 fatal injuries and 292 major injuries were reported in British farmers or farmworkers in -2014(HSE, 2014, and a recent survey by the British Equine Veterinary Association revealed that on average, equine vets sustain seven to eight work-related injuries during a 30 year period (BEVA, 2014), highlighting just how hazardous these environments can be. Few data are available on occupational injuries in the British veterinary profession; however, when working in what could be interpreted as a high-risk environment, a constant exposure to risk for those living or working in these types of environment may lead to habituation to, or normalisation of risk (Clouser et al, 2015). Individuals in this study who tended to grade common clinical scenarios as posing a moderate to high risk of zoonosis exposure were also more likely to "just hope for the best", perhaps suggesting they have normalised these situations and do not perceive them as requiring additional precautions.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 7 fatal injuries and 292 major injuries were reported in British farmers or farmworkers in -2014(HSE, 2014, and a recent survey by the British Equine Veterinary Association revealed that on average, equine vets sustain seven to eight work-related injuries during a 30 year period (BEVA, 2014), highlighting just how hazardous these environments can be. Few data are available on occupational injuries in the British veterinary profession; however, when working in what could be interpreted as a high-risk environment, a constant exposure to risk for those living or working in these types of environment may lead to habituation to, or normalisation of risk (Clouser et al, 2015). Individuals in this study who tended to grade common clinical scenarios as posing a moderate to high risk of zoonosis exposure were also more likely to "just hope for the best", perhaps suggesting they have normalised these situations and do not perceive them as requiring additional precautions.…”
Section: Discussionmentioning
confidence: 99%
“…The risk assessment is a key feature as specified in several aspects of the Directive, such as: identification of risks, worker participation, development of suitable measures having as a priority the elimination of risks' sources, documentation, and periodic audit of risks in workplaces [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Our findings around farming-related injuries confirm those from international studies, in terms of the most common mechanisms for injury being agricultural machinery (including vehicles), interaction with livestock and falls. 3,7,8,[17][18][19][20][21][22] Our study has identified some high-risk mechanisms for injury, regardless of whether individuals were undertaking a farming activity or not. In summary, some of the key risks in the Midland region are for:…”
Section: Discussionmentioning
confidence: 83%